Kegiatan Jam Wajib Belajar Sebagai Sarana Belajar Mandiri di Pondok Pesantren Raudlatul Ulum 1 Putri - Sofiana Sofiana (Pusat Riset dan Inovasi Nasional, 2025)
Finding out “persepsi santri” at Islamic Boarding School Raudlatul Ulum 1 Putri about the Compulsory Study Hour activity as a self-study method was the aim of this study. This study employed a qualitative methodology, gathering data through documentation, interviews, and observation. The findings demonstrated that students benefited greatly from the Compulsory Study Hour exercise, which enhanced their capacity to focus, comprehend the subject matter, and study on their own. However, several problems hindered the Compulsory Study Hour activity, such as tired students, monotonous learning methods, and lack of mentors. To make this activity more effective, it is recommended to add variations in learning methods, provide adequate mentors, and give students sufficient rest time.